How cooperative innovation could be more effective in China: a relationship perspective. Issue 8 (4th January 2021) - Chi, Rui; Zhang, Jianyu; Deng, Guangkuan
Abstract : Purpose: Considering strategic information sharing (SIS), this paper aims to develop a better understanding of how relation-specific investments (RSIs) influence cooperative innovation performance (CIP) in downstream channel relationships. Also examined was the moderating effect of relational trust in that the indigenous practice of guanxi is especially critical in China. Design/methodology/approach: Data were collected through a questionnaire in Chinese high-tech industries, with a valid response from 310 companies. A hierarchical regression analysis was used to test the conceptual model and hypotheses, combining mediation and moderation analysis. Findings: Results show that the influences of specific investments vary according to the specificity dimensions examined. Specifically, human RSI influences CIP and SIS most significantly, and the impact of procedural RSI is, relatively, the weakest. Relational trust's moderating role is confirmed, and SIS plays a partially mediating role in enhancing vertical cooperative innovation. Practical implications: Managers should know clearly different roles of RSIs in inter-firm cooperative innovation and prioritize human RSI and brand RSI when investing into channels. More importantly, the findings reveal that strategy-level information sharing should be valued more. It is also recommended that relational ties are vital, especially in Chinese business context. Originality/value: To the best of the authors' knowledge, this paper is among the first few to investigate how the effects of disaggregated RSIs in inter-firm cooperative innovation vary and the importance of SIS in vertical relationships. The results provide insightful guidance for researchers and managers in how to better manage RSIs to improve CIP.